The Startup Owner's Manual: The Step-By-Step Guide for Building a Great Company - Steve Blank; Bob Dorf (USA Wiley, 2020)
Now a decade after the Four Steps to the Epiphany sparked the Lean Startup revolution, comes its sequel... The Startup Owner's Manual The Manual incorporates 10 years of learning and best practices that have swept the startup world. It: Incorporates the "Business Model Canvas" as the organizing principle for startup hypotheses Provides separate paths and advice for web/mobile products versus physical products Offers a wealth of detailed instruction on how to get, keep, and grow customers recognizing the different techniques for web and physical channels And teaches a "new math" for startups: "metrics that matter for fueling growth" The Startup Owner's Manual is a step-by-step, near-encyclopedic reference manual or "how to" for building a successful, scalable startup. Want to know what to do the first, week, month or year? What's the right distribution channel for your product? How to get traffic to your web site? ...and how to activate customers or users on arrival? Who are the right "first customers," and why? ...plus many more great tips in nearly 500 pages, complete with index, glossary, and Customer Development Checklists It's the indispensible reference guide for any startup founder, entrepreneur, investor or educator.
Keywords: Business; Entrepreneurship; Nonfiction